Safety of two-hour intermittent intravenous infusions of tacrolimus in the allogeneic hematopoietic stem cell transplantation unit. (January 2021) - Bacopoulos, Alexander JS; Ho, Lina; Yang, Anjie; Ng, Pamela; Dara, Celina; Loach, David; Deotare, Uday; Michelis, Fotios V; Viswabandya, Auro; Kim, Dennis D; Lipton, Jeffrey H; Messner, Hans A; et al.
At our institution, tacrolimus is used as a second-line agent for the prevention and treatment of graft-versus-host-disease in the allogeneic hematopoietic stem cell transplantation (HSCT) unit after patients have experienced a serious or intolerable adverse event to cyclosporine. As per our standard practice, tacrolimus is administered via 2-h intermittent IV infusions (IIVs) every 12 h rather than continuous IV infusion. Shorter infusion times are cautioned due to concerns of higher rates of nephrotoxicity, neurotoxicity and infusion-related reactions, although there is a paucity of data to support this claim. Our primary objective was to evaluate the safety of a 2-h IIV of tacrolimus in an adult HSCT population. We retrospectively reviewed the charts of 104 patients who received tacrolimus by IIV (3574 doses; median = 22, range 1–158, IQR = 28) from 2002 to 2016. Primary outcomes collected include rates of nephrotoxicity, neurotoxicity and infusion-related reactions. One (0.9%) grade 2 infusion-related reaction occurred and resolved without discontinuation of tacrolimus. Of 16 incidences (13.6%) of nephrotoxicity, all but 10 (8.5%) cases resolved. Precipitating factors for nephrotoxicity unrelated to tacrolimus were identified in all 10 cases. There were 41 incidences (35%) of neurotoxicity, of which, 8 (6.8%) were considered serious. All neurotoxicity reverted to baseline or resolved completely. We propose that a 2-h IIV of tacrolimus is a safe method of administration in the adult HSCT setting.